The Relationship between Scout Extracurriculars and Discipline of Class V Students at State Elementary School 161 Pekanbaru - Sari, Risna; Ramadan, Zaka Hadikusuma (CV. Rayyan Dwi Bharata, 2024)
Discipline is an attitude that requires a person to be responsible for their actions, obey rules and respect time. Awareness of enforcing discipline can be trained with positive activities held by schools through extracurricular scout skills. The aim of this research is to determine the relationship between scout extracurricular activities and the discipline of class V students at State Elementary School 161 Pekanbaru. This research uses a quantitative type of research. The data collection technique used was a questionnaire given by 62 respondents containing 17 scout extracurricular statements and 24 student disciplinary statements which would be answered by students in class V of SDN 161 Pekanbaru. Determining the sample in this study used a total sampling technique because all members of the population were used as samples in this study. The research results show that there is a positive and significant relationship between scout extracurricular activities and student discipline. The correlation coefficient obtained is 0.501, which means the calculated r obtained is greater than the r table which has been determined at a significance level of 5% with a calculated r calculated of 0.501 0.250, this means r calculated r table which means Ho is rejected and Ha is accepted. Based on these results, it can be concluded that there is a relationship between scout extracurricular activities and the discipline of class V students at State Elementary School 161 Pekanbaru.